Preparation method and application of PTFE filter material loaded with Mn-Fe-CeOx composite metal oxide
By functionalizing the surface of the PTFE filter material and loading the Mn-Fe-CeOx composite metal oxide catalyst through hydrothermal reaction, the problems of complex preparation of catalytic filter material, low-temperature activity and poor sulfur resistance in the prior art are solved, and efficient low-temperature denitrification and sulfur resistance are achieved.
Patent Information
- Application Number
- CN202410947280.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-07-16
AI Technical Summary
The existing integrated catalytic filter material preparation methods are complex, and the low-temperature activity and sulfur resistance are not outstanding.
The surface functionalization modification of polydopamine and tanninic acid and hydrothermal reaction of PTFE filter material fibers is uniformly supported by Mn-Fe-CeOx composite metal oxide denitrification catalyst, combining iron salts and cerium salts to dopant and modification of manganese oxides.
The high and low temperature denitrification activity and sulfur resistance are improved, and the catalyst and filter material are firmly combined, which are suitable for the treatment of high-sulfur industrial flue gas.
Smart Images

Figure CN118846665B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic filtering materials, and in particular to a preparation method and application of a PTFE filter material loaded with a Mn-Fe-CeOx composite metal oxide. Background Art
[0002] Flue gas particles and nitrogen oxides (NO x , x = 1,2), carbon oxides, sulfur dioxide (SO2), etc. are one of the main causes of air pollution. Among them, high-temperature gas emissions from coal-fired power generation, cement and other industries are particulate pollutants and NO x The main sources of emissions are garbage incineration plants, non-ferrous metallurgical plants and other stationary sources of NO x Emissions of NO also cannot be ignored. Currently, a series of NO x Removal technology. Among them, selective catalytic reduction (SCR) is used to remove NO x Reduction to N2 and water, NH3 as a reducing agent, is considered one of the most promising technologies due to its high conversion rate, good selectivity and practicality. Bag filter materials made of non-woven materials play a key role in the prevention and control of dust particle pollutants. They have high dust removal efficiency and the dust emission concentration after treatment is less than 30mg / m 3 . In the traditional industrial flue gas treatment system, dust removal and nitrogen oxide removal are carried out in two parts, which takes up a large area, has high investment costs and a complex process. If the filter material is given a denitrification function on the basis of its original dust removal function, and nitrogen oxides are removed while removing dust particle pollutants in industrial flue gas, it will greatly simplify the flue gas treatment system in the existing technology, save the space and capital investment of denitrification equipment, and reduce the cost of industrial flue gas treatment. Therefore, the research on dust removal and denitrification functional filter materials is of great practical significance.
[0003] In order to explore the new technology of integrated dust removal and denitrification filter material, researchers have conducted a lot of research work. Patent application number 201310120061.7 discloses a catalytic filter material with denitrification and dust removal functions and its preparation method, which uses carbon nanotubes as catalyst carriers, and obtains MnOx / CNTs low-temperature denitrification catalyst by liquid phase coprecipitation method, and then loads the catalyst on the filter material by impregnation; Patent application number 201410218348.8 discloses a method for in-situ production of denitrification catalyst on filter material, which forms an active coating layer on the surface of the filter material through the oxidative self-polymerization of dopamine, and then uses polydopamine and diisocyanate to form a denitrification catalyst. The chelation of manganese ions and the strong oxidation of potassium permanganate generate MnO2 catalyst in situ on the surface of the filter material; the patent with application number 202310367010.8 discloses a method for preparing a Pickering-type SCR catalytic functional emulsion containing composite metal oxide particles, using composite metal oxide particles prepared by wet chemical method as emulsifier, water as continuous phase, and water-insoluble organic solvent as dispersed phase. After high-speed shear emulsification, a stable O / W type catalytic functional emulsion is obtained, and it is loaded on the surface of a variety of filter material carriers. It should be noted that the existing integrated catalytic filter materials for denitrification and dust removal mainly adopt ultrasonic impregnation method and room temperature synthesis. Most of these methods are carried out step by step, with complex processes, large catalyst loading, uneven distribution, and the low-temperature effect of active components is not prominent, and the sulfur resistance is poor. Therefore, it is the focus and difficulty of the current research to obtain a low-load, high-activity and sulfur-resistant, firmly loaded integrated catalytic filter material for denitrification and dust removal by a simple loading method. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing an integrated catalytic filter material for denitrification and dust removal, which has high low-temperature denitrification activity and sulfur resistance and combines a catalyst with a filter material, and its application, so as to solve the problems mentioned in the above technical background that the catalytic filter material preparation method of the prior art method is complex, and the low-temperature activity and sulfur resistance are not outstanding.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing a PTFE filter material loaded with a Mn-Fe-CeOx composite metal oxide comprises the following steps: using a PTFE needle-punched filter material as a carrier, uniformly loading a manganese-iron-cerium composite metal oxide denitration catalyst on the surface of the filter material fiber through surface functionalization modification of polydopamine and tannic acid and hydrothermal reaction, which does not destroy the physicochemical properties and structure of the original filter material, retains its dust removal function as a bag filter, and activates the originally inert polymer fiber surface. After being loaded with the manganese-iron-cerium composite metal oxide denitration catalyst, the surface exhibits higher low-temperature denitration activity and sulfur resistance, and the catalyst is firmly combined with the filter material under the strong bonding effect of polydopamine and tannic acid.
[0007] Specifically, the above preparation method comprises the following steps:
[0008] (1) Immerse the cleaned PTFE filter material in an alkaline solution of dopamine and tannic acid and stir it at a certain temperature for a period of time so that the surface of the filter material fiber is evenly coated with a polymer functional layer;
[0009] (2) After the polymer-modified PTFE filter material is taken out from the solution, it is rinsed with deionized water and ethanol and dried;
[0010] (3) The dried filter material in step (2) is immersed in deionized water, and cerium salt, iron salt and potassium permanganate are added in sequence, and the mixture is stirred for a period of time at room temperature, and then allowed to stand for a period of time.
[0011] (4) The entire solution containing the filter material in step (3) is transferred to a hydrothermal reaction kettle, and placed in an oven for hydrothermal reaction at a certain temperature for a period of time to make Mn-Fe-CeO x The composite metal oxide catalyst is formed in situ on the surface of the filter media fibers and is firmly attached.
[0012] (5) After the hydrothermal reactor in step (4) is cooled to room temperature, the Mn-Fe-CeO x The modified PTFE filter material of the composite metal oxide catalyst is rinsed with deionized water and ethanol, and then activated and dried at a certain temperature to obtain a catalytic filter material with good low-temperature denitrification function and good sulfur resistance.
[0013] Preferably, the concentration of dopamine in step (1) is 0.1-10 g / L, the concentration of tannic acid is 0-2 g / L, the solvent in the alkaline solution is a mixture of deionized water and ethanol in any proportion, and one or more compounds selected from sodium hydroxide, potassium hydroxide, ammonia water or tris(hydroxymethyl)aminomethane are added thereto to adjust the pH value to between 8 and 11.
[0014] Preferably, the stirring temperature in step (1) is between 0-100° C., and the stirring reaction time is between 0.5-48 h.
[0015] Preferably, the drying temperature in step (2) is between 50-150° C., and the drying time is between 0.5-48 h.
[0016] Preferably, the iron salt in step (3) is selected from one or more of ferric chloride, ferric nitrate, ferric sulfate, ferrous chloride, ferrous nitrate and ferrous sulfate; the cerium salt is selected from one or more of cerium chloride, cerium nitrate and cerium acetate; and the mass ratio of the filter material to potassium permanganate is controlled to be between 2:1-20:1, the molar ratio of the iron salt to potassium permanganate is between 0:1-1:1; and the molar ratio of the iron salt to potassium permanganate is between 0:1-1:1.
[0017] Preferably, the stirring reaction time in step (3) is 0.5-48h; and the standing time is 0.5-48h.
[0018] Preferably, the hydrothermal reaction temperature in step (4) is 80-180° C.; and the hydrothermal reaction time is 0.5-48 h.
[0019] Preferably, the activation and drying temperature in step (5) is between 120-180° C., and the drying time is between 0.5-48 h.
[0020] Another object of the present invention is to provide an application of the PTFE filter material prepared by the above method in dust removal and denitrification.
[0021] Beneficial effects of the present invention:
[0022] 1. The manganese-iron-cerium composite metal oxide denitrification catalyst was successfully loaded on the surface of the filter material fiber through surface functional modification and hydrothermal reaction of polydopamine and tannic acid. It will not destroy the physical and chemical properties and structure of the original filter material, retaining its dust removal function as a bag dust collector, and activate the originally inert polymer fiber surface to make the catalyst evenly dispersed on the filter material surface and firmly bonded.
[0023] 2. The manganese-based ternary metal oxide denitrification catalyst prepared by doping and modifying manganese oxide with iron salt and cerium salt has excellent low-temperature denitrification activity and sulfur resistance, and therefore has broad application prospects in the environment of high-sulfur industrial flue gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described below in conjunction with the accompanying drawings.
[0025] Figure 1 The loaded Mn-Fe-CeO of Example 4 of the present invention x SEM image of PTFE filter material with composite metal oxides.
[0026] Figure 2 The loaded Mn-Fe-CeO of Example 4 of the present invention x Element distribution spectrum of PTFE filter material with composite metal oxides.
[0027] Figure 3This is a diagram showing the anti-sulfur effect of the filter materials of Example 4, Comparative Example 1 and Comparative Example 2 of the present invention under 180° C. and 150 ppm SO2 atmosphere conditions. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] The cleaned 1.3g PTFE filter material was immersed in a water and ethanol mixed solution (water and ethanol volume ratio of 15:1) of 8g / L dopamine and 0.2g / L tannic acid, and the pH value was adjusted to about 8.5 by adding ammonia water, and stirred at room temperature for 12h, then taken out, rinsed with deionized water and ethanol, and dried at 60℃ for 12h; the dried filter material was immersed in deionized water again, 0.12g cerium acetate, 0.09g ferric chloride and 0.28g potassium permanganate were added in sequence, and stirred at room temperature for 20h, and then continued to stand for 10h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 120℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 60℃ for 12h to obtain a Mn-Fe-CeO-loaded composite filter material. x PTFE filter material with composite metal oxides.
[0031] Example 2
[0032] The cleaned 1.3g PTFE filter material was immersed in a mixed solution of water and ethanol (the volume ratio of water to ethanol was 10:1) containing 4g / L dopamine, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.02g cerium chloride, 0.09g ferric chloride and 0.28g potassium permanganate were added in sequence, and stirred continuously at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 140℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-Fe-CeO-loaded composite filter material. x PTFE filter material with composite metal oxides.
[0033] Example 3
[0034] About 1.3g of cleaned PTFE filter material was immersed in a mixed solution of water and ethanol (volume ratio of water to ethanol was 10:1) containing 4g / L dopamine and 0.1g / L tannic acid, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.16g of cerium chloride, 0.09g of ferric chloride and 0.28g of potassium permanganate were added in sequence, and stirred continuously at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 140℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-Fe-CeO-loaded composite filter material. x PTFE filter material with composite metal oxides.
[0035] Example 4
[0036] About 1.3g of cleaned PTFE filter material was immersed in a mixed solution of water and ethanol (volume ratio of water to ethanol was 10:1) of 4g / L dopamine and 0.1g / L tannic acid, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.09g of cerium chloride, 0.09g of ferric chloride and 0.28g of potassium permanganate were added in sequence, and stirred continuously at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 140℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-Fe-CeO-loaded composite filter material. x PTFE filter material with composite metal oxides.
[0037] like Figure 1 and Figure 2 Shown are the SEM image and element distribution spectrum of the filter material obtained in Example 4.
[0038] Example 5
[0039] About 1.3g of cleaned PTFE filter material was immersed in a mixed solution of water and ethanol (volume ratio of water and ethanol was 1:1) of 2g / L dopamine and 1g / L tannic acid, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.09g of cerium chloride, 0.24g of ferric nitrate and 0.28g of potassium permanganate were added in sequence, and stirred continuously at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 160℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-Fe-CeO-loaded composite filter material. x PTFE filter material with composite metal oxides.
[0040] Example 6
[0041] The cleaned 1.3g PTFE filter material was immersed in a mixed solution of water and ethanol (the volume ratio of water to ethanol was 10:1) containing 4g / L dopamine, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.09g cerium acetate, 0.08g ferrous sulfate and 0.28g potassium permanganate were added in sequence, and stirred at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 120℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-Fe-CeO-loaded composite filter material. x PTFE filter material with composite metal oxides.
[0042] Comparative Example 1
[0043] The cleaned 1.3g PTFE filter material was immersed in a mixed solution of water and ethanol (the volume ratio of water to ethanol was 10:1) containing 4g / L dopamine, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.09g ferric chloride and 0.28g potassium permanganate were added in sequence, and stirred continuously at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 140℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-FeO loaded filter material. xPTFE filter material with composite metal oxides.
[0044] Comparative Example 2
[0045] About 1.3g of cleaned PTFE filter material was immersed in a mixed solution of water and ethanol (volume ratio of water and ethanol was 10:1) containing 4g / L dopamine, and the pH value was adjusted to about 9 by adding ammonia water, and stirred at room temperature for 24h, then taken out, rinsed with deionized water and ethanol, and dried at 80℃ for 12h; the dried filter material was immersed in deionized water again, 0.09g of cerium chloride and 0.28g of potassium permanganate were added in sequence, and stirred continuously at room temperature for 0.5h, and then continued to stand for 12h. Finally, the entire solution containing the filter material was transferred to a hydrothermal reactor, and placed in an oven at 140℃ for hydrothermal reaction for 12h, and the composite filter material was taken out after cooling, and washed and dried, and dried at 80℃ for 12h to obtain a Mn-CeO loaded filter material. x PTFE filter material with composite metal oxides.
[0046] like Figure 3 As shown, it is a diagram of the anti-sulfur effect of the filter materials of Example 4, Comparative Example 1 and Comparative Example 2 under 180°C and 150ppm SO2 atmosphere conditions.
[0047] Denitrification activity test
[0048] The catalytic composite filter materials prepared in the above examples and comparative examples were tested for denitration activity. The test conditions were as follows: the volume fractions of NO and NH3 were both 0.05%, the volume fraction of O2 was 5%, and the rest was N2. The gas flow rate was 400 mL min -1 After the airflow stabilized for 30 minutes, the concentration of inlet and outlet nitrogen oxides was measured with a German M60x flue gas analyzer to calculate the denitrification rate of the catalytic composite filter material. The test temperature was in the low temperature range of 100-180℃. The test results are shown in the following table:
[0049]
[0050]
[0051] The above specific implementation method part specifically introduces the analytical method involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the method and ideas of the present invention, rather than limiting the relevant content. Without departing from the principle of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a PTFE filter material loaded with a Mn-Fe-CeOx composite metal oxide, characterized in that: Using PTFE needle-punched filter media as carrier, the manganese-iron-cerium composite metal oxide denitrification catalyst was uniformly loaded on the filter media fiber surface through surface functional modification of polydopamine and tannic acid and hydrothermal reaction. The specific steps include: (1) Immerse the cleaned PTFE filter material in an alkaline solution of dopamine and tannic acid and stir it at a certain temperature for a period of time so that the surface of the filter material fiber is evenly coated with a polymer functional layer; (2) After the polymer-modified PTFE filter material is taken out from the solution, it is rinsed with deionized water and ethanol and dried; (3) immersing the dried filter material in step (2) in deionized water, adding cerium salt, iron salt and potassium permanganate in sequence, stirring at room temperature for a period of time, and then allowing to stand for a period of time; (4) transferring the entire solution containing the filter material in step (3) to a hydrothermal reaction kettle, and placing it in an oven for hydrothermal reaction at a certain temperature for a period of time; (5) After the hydrothermal reactor in step (4) is cooled to room temperature, the Mn-Fe-CeO x The modified PTFE filter material of the composite metal oxide catalyst is rinsed with deionized water and ethanol, activated and dried at a certain temperature to obtain the filter material.
2. The method for preparing a PTFE filter material loaded with a Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The concentration of dopamine in step (1) is 0.1-10 g / L, the concentration of tannic acid is 0-2 g / L, the solvent in the alkaline solution is a mixture of deionized water and ethanol in any proportion, and one or more compounds selected from sodium hydroxide, potassium hydroxide, ammonia water or tris(hydroxymethyl)aminomethane are added thereto to adjust the pH value to between 8 and 11.
3. The method for preparing a PTFE filter material loaded with a Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The stirring temperature in step (1) is between 0-100° C., and the stirring reaction time is between 0.5-48 h.
4. The method for preparing a PTFE filter material loaded with a Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The drying temperature in step (2) is between 50-150° C., and the drying time is between 0.5-48 h.
5. The method for preparing a PTFE filter material loaded with Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The iron salt described in step (3) is selected from one or more of ferric chloride, ferric nitrate, ferric sulfate, ferrous chloride, ferrous nitrate and ferrous sulfate; the cerium salt is selected from one or more of cerium chloride, cerium nitrate and cerium acetate; and the mass ratio of the filter material to potassium permanganate is controlled to be between 2:1-20:1, the molar ratio of the iron salt to potassium permanganate is between 0:1-1:1; and the molar ratio of the iron salt to potassium permanganate is between 0:1-1:
1.
6. The method for preparing a PTFE filter material loaded with Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The stirring reaction time in step (3) is 0.5-48h; the standing time is 0.5-48h.
7. The method for preparing a PTFE filter material loaded with Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The hydrothermal reaction temperature in step (4) is 80-180° C.; the hydrothermal reaction time is 0.5-48 h.
8. The method for preparing a PTFE filter material loaded with Mn-Fe-CeOx composite metal oxide according to claim 1, characterized in that: The activation and drying temperature in step (5) is between 120-180° C., and the drying time is between 0.5-48 h.
9. Application of the PTFE filter material prepared according to the preparation method according to any one of claims 1 to 8 in dust removal and denitrification.
Citation Information
Patent Citations
Catalytic filtration material with denitration and dust removal functions and preparation method of catalytic filtration material
CN103191603A
Method for generating denitration catalyst on filter material in situ
CN103949115A
Preparation method of Pickering type SCR (Selective Catalytic Reduction) catalytic functional emulsion containing composite metal oxide particles
CN116637613A
Preparation method of denitration demercuration integral filter material
CN108926911A
Preparation method of non-woven air filtering material with formaldehyde removal function
CN116371083A